2001
DOI: 10.1139/t00-076
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility and hydraulic conductivity of a chemically treated expansive clay

Abstract: The paper presents a series of laboratory tests and evaluates the effect of lime and fly ash on the compressibility and hydraulic characteristics of an expansive soil in Cyprus. The tests were performed at different percentages of lime (0–7%) and fly ash (15 and 25%) by dry weight of soil, and additional tests were also performed on soils treated with 15% fly ash plus 3% lime. Previously published research reveals that few data are available concerning the compressibility and hydraulic conductivity of lime-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 9 publications
2
47
1
3
Order By: Relevance
“…The rate of exchange depends on clay type, solution concentrations and temperature (Gomez, 2009). In soil stabilization studies, CEC values have been used to a limited extent to explain the effectiveness of soil stabilization (Nalbantoglu and Tuncer, 2001;Al-Rawas et al, 2002;Nalbantoglu, 2004;Gomez, 2009).…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of exchange depends on clay type, solution concentrations and temperature (Gomez, 2009). In soil stabilization studies, CEC values have been used to a limited extent to explain the effectiveness of soil stabilization (Nalbantoglu and Tuncer, 2001;Al-Rawas et al, 2002;Nalbantoglu, 2004;Gomez, 2009).…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
“…It can be seen that lime and CFA had the highest and the lowest SSA values, respectively. A higher SSA indicates more reactivity of additive (Nalbantoglu and Tuncer, 2001;Sreekrishnavilasam et al, 2007).…”
Section: Specific Surface Areamentioning
confidence: 99%
“…Le traitement à la chaux permet aussi de réduire, voire de supprimer, le gonflement des sols argileux (Brandi 1981 ;Nalbantoglu et Tuncer, 2001 ;Rao et Thyagaraj, 2003). Ainsi, le traitement à la chaux pour rait être intéressant pour prévenir le gonflement des sols argileux dans le cadre de leur emploi en terras sement.…”
Section: Introductionunclassified
“…ratio between height increase due to wetting to initial height, of an expansive soil reduced from 34.5% to about 26.5% in specimens mixed with 10% of limestone, and from 34.5% to about 1% in specimens with 10% of hydrated lime. Also, Nalbantoglu & Tuncer (2001) found that the swelling potential was drastically reduced from 20% for the untreated specimen to 1.5% when treated with 2% of lime with no curing time.…”
Section: List Of Figuresmentioning
confidence: 95%
“…In fact, some researchers have shown that lime treatment may reduce the swelling potential of expansive soils (Holt et al, 2000;Al-Rawas et al, 2005;Panjaitan, 2014, Schanz & Elsawy, 2015, Nalbantoglu & Tuncer, 2001). For instance, Schanz & Elsawy (2015) concluded that the swelling potential, i.e.…”
Section: List Of Figuresmentioning
confidence: 99%